2022
DOI: 10.1245/s10434-022-11439-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Arterial Infusion Pump Chemotherapy for Unresectable Intrahepatic Cholangiocarcinoma: A Systematic Review and Meta-Analysis

Abstract: Background Patients with unresectable intrahepatic cholangiocarcinoma (iCCA) have poor survival. This systematic review describes the survival outcomes of hepatic arterial infusion pump (HAIP) chemotherapy with floxuridine for patients with unresectable iCCA. Patients and Methods A literature search was conducted using the electronic databases PubMed, Medline (Ovid), Embase, Web of Science, Google Scholar, and Cochrane to find studies that reported data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…14,15,24,28 Furthermore, a meta-analysis showed that HAIC achieved a pooled PR and the weighted median PFS of 52.7% and 11.4 months, respectively. 29 Despite different criteria for the response rate, treatment efficacy of the HAIC-based triple-combination therapy in our study was better than that of the majority of previous studies. However, it should be noted that in previous studies, patients had received surgical HAIC pump placement and regional lymphadenectomy, unlike our patients.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…14,15,24,28 Furthermore, a meta-analysis showed that HAIC achieved a pooled PR and the weighted median PFS of 52.7% and 11.4 months, respectively. 29 Despite different criteria for the response rate, treatment efficacy of the HAIC-based triple-combination therapy in our study was better than that of the majority of previous studies. However, it should be noted that in previous studies, patients had received surgical HAIC pump placement and regional lymphadenectomy, unlike our patients.…”
Section: Discussioncontrasting
confidence: 75%
“…In previous studies on HAIC for ICC, the PR based on RECIST was reported to be 27.3%–59.5%, and the median PFS was 7.4–12.8 months 14,15,24,28 . Furthermore, a meta‐analysis showed that HAIC achieved a pooled PR and the weighted median PFS of 52.7% and 11.4 months, respectively 29 . Despite different criteria for the response rate, treatment efficacy of the HAIC‐based triple‐combination therapy in our study was better than that of the majority of previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…This small sample study suggested the feasibility of HAIC in iCCA treatment. A recent meta-analysis (pooling data from 9 studies that had enrolled a total of 154 patients) showed that hepatic arterial infusion pump (HAIP) chemotherapy with floxuridine for patients with unresectable iCCA was associated with a favorable 3-year OS of 39.5% (95% CI 31.5–47.4%) compared with systemic chemotherapy, with no patients surviving beyond 3 years observed in the ABC trial [ 31 ]. Therefore, we further explored the application of HAIC based on the FOLFIRI regimen in iCCA patients as a second-line and successive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recent advances in our understanding of the genomic landscape in ICC have also led to the implementation of targeted therapies for up to 40% of patients with actionable alterations, including those in isocitrate dehydrogenase (IDH) and fibroblast growth factor receptor (FGFR), but resistance to these agents typically develops within months of initiation, and survival remains poor. [22][23][24][25] Emerging effective treatment strategies that combine systemic and locoregional therapies, such as radioembolization or hepatic artery infusion (HAI), have also been developed 20,26,27 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%